2020
DOI: 10.1111/sms.13678
|View full text |Cite
|
Sign up to set email alerts
|

The effect of previous shoulder pain on supraspinatus tendon thickness changes following swimming practice

Abstract: Objectives To assess if swimming practice results in changes in supraspinatus tendon thickness, acromiohumeral distance, and occupational ratio in shoulders of elite swimmers with and without a history of shoulder pain. Design Case‐Control study. Methods A convenience sample of fifty elite swimmers (14‐22 years) were recruited for this study. Groups were defined by the presence (history of pain, N = 37) or absence (pain free, N = 63) of significant interfering shoulder pain within the previous 6 months. The cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 28 publications
4
23
0
Order By: Relevance
“…Further to this it has been found that STT changes following a swimming practice are significantly different in those swimmers with a history of shoulder pain 9 . While both pain free shoulders and shoulders with a history of pain increased in STT following practice, those shoulders with a history of pain showed a greater increase in STT following practice and remained thicker at six hours post practice 9 . Given that STT responds to swimming load and its capability to return to baseline may be compromised in individuals with a history of shoulder pain, it is postulated that monitoring the thickness of the tendon could be an effective tool for assessing the response of the shoulder to a given training load.…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…Further to this it has been found that STT changes following a swimming practice are significantly different in those swimmers with a history of shoulder pain 9 . While both pain free shoulders and shoulders with a history of pain increased in STT following practice, those shoulders with a history of pain showed a greater increase in STT following practice and remained thicker at six hours post practice 9 . Given that STT responds to swimming load and its capability to return to baseline may be compromised in individuals with a history of shoulder pain, it is postulated that monitoring the thickness of the tendon could be an effective tool for assessing the response of the shoulder to a given training load.…”
Section: Introductionmentioning
confidence: 66%
“…Findings have demonstrated that subjects with painful rotator cuff tendinopathy had a significantly greater increase in supraspinatus tendon thickness (STT) at one and six hours following a loading protocol (McCreesh et al, 2017). Further to this it has been found that STT changes following a swimming practice are significantly different in those swimmers with a history of shoulder pain 9 . While both pain free shoulders and shoulders with a history of pain increased in STT following practice, those shoulders with a history of pain showed a greater increase in STT following practice and remained thicker at six hours post practice 9 .…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Thus, understanding possible mechanisms behind increases in SST thickness yields valuable information for managing throwing-related rotator cuff tendon injuries. SST thickness has been measured using ultrasound imaging [29,[31][32][33], which is a reliable tool to study for this purpose [34,35]. Given the various tissue mechanism of glenohumeral ROM alterations and the likelihood of throwing shoulder injuries on the SST, specific glenohumeral ROM might be associated with SST thickness measured with ultrasound.…”
Section: Supraspinatus Tendon Changes and Glenohumeral Range Of Motion In College Baseball Playersmentioning
confidence: 99%